Genome-Wide Analysis of the PvHsp20 Family in Switchgrass: Motif, Genomic Organization, and Identification of Stress or Developmental-Related Hsp20s - Yan, Haidong; Zhang, Ailing; Chen, Jing; He, Xiaoyan; Xu, Bin; Xie, Guanqi; Miao, Zhiming; Zhang, Xinquan; Huang, Linkai (Frontiers in Plant Science, 2017)
Hsp20 proteins exist in all plant species and represent the most abundant small heat shock proteins (sHSPs) in plants. Hsp20s were known as chaperones maintaining cellular homeostasis during heat or other kinds of abiotic stresses. The objective of this study was to understand the phylogenetic relationship, genomic organization, diversification of motif modules, genome localization, expression profiles, and interaction networks of switchgrass (Panicum virgatum L.) Hsp20s (PvHsp20s). A total of 63 PvHsp20s were identified with their consensus as well as unique ACD motifs and gene structures analyzed. Most PvHsp20s (87%) were responsive to heat and other kinds of abiotic stresses. When under optimum growth condition, 38 of them displayed relative higher expression levels in inflorescence and seeds, suggesting their protective roles in the stress-sensitive reproductive organs. An in silico analysis of interaction network of PvHsp20 proteins further revealed potential interactive proteins, including stress-inducible ones in the network. Furthermore, PvHsp20 genes unevenly distributed in two sets of homeologous chromosomes, and only segmental duplication was found among the paralogous gene pairs, reflecting that the allotetraploidization of switchgrass allowed the accumulation of PvHsp20s that in turn facilitated its successful adaptation in hot and dry plateaus of North America. The present results provided an insight into PvHsp20s with an emphasis on the uniqueness of this gene family in switchgrass. Such information shall also be useful in functional studies of PvHsp20 genes and molecular breeding of switchgrass.